2016
DOI: 10.1128/aac.02462-15
|View full text |Cite
|
Sign up to set email alerts
|

Escape Mutations in NS4B Render Dengue Virus Insensitive to the Antiviral Activity of the Paracetamol Metabolite AM404

Abstract: Despite the enormous disease burden associated with dengue virus infections, a licensed antiviral drug is lacking. Here, we show that the paracetamol (acetaminophen) metabolite AM404 inhibits dengue virus replication. Moreover, we find that mutations in NS4B that were previously found to confer resistance to the antiviral compounds NITD-618 and SDM25N also render dengue virus insensitive to AM404. Our work provides further support for NS4B as a direct or indirect target for antiviral drug development. Dengue v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Intriguingly, as summarized in Fig. 10, except for F164L, which confers DENV resistance to SDM25N and AM404 and localizes at the cytosolic loop between TMD3 and TMD4 (65,67), all other drug resistance mutations are mapped in the transmembrane domains. Furthermore, except for DENV V63 and YFV P219 mutations, which specifically confer resistance to spiropyrazolopyridone compound-14a and BDAA, respectively, all other DENV and YFV drug resistance mutations identified thus far confer resistance to multiple drugs (25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intriguingly, as summarized in Fig. 10, except for F164L, which confers DENV resistance to SDM25N and AM404 and localizes at the cytosolic loop between TMD3 and TMD4 (65,67), all other drug resistance mutations are mapped in the transmembrane domains. Furthermore, except for DENV V63 and YFV P219 mutations, which specifically confer resistance to spiropyrazolopyridone compound-14a and BDAA, respectively, all other DENV and YFV drug resistance mutations identified thus far confer resistance to multiple drugs (25).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, several structurally distinct compounds have been identified that inhibit DENV or YFV replication through targeting NS4B (40,(63)(64)(65)(66)(67). In addition, multiple inhibitors of the NS4B protein of hepatitis C virus, a distantly related member of the Flaviviridae family, are currently under preclinical and clinical development for treatment of hepatitis C infection (68).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the N-terminal 125amino-acid domain of DENV NS4B was indicated to be responsible for inhibition of the immune response (25). Notably, several structurally distinct compounds have been identified to inhibit flavivirus replication by intensively targeting the TMD of NS4B (26)(27)(28)(29)(30)(31)(32). It is thus conceivable that inhibitors targeting TMD of NS4B would perturb its function, leading to the suppression of viral RNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological activities on eukaryotic cells have previously been reported for AM404, including activating the capsaicin receptor TRPV1, inhibiting COX, activating cannabinoid receptors, inhibiting cellular anandamide reuptake, and inhibiting NFAT activity and IκB kinase beta phosphorylation and activation (Bertolini et al, ; Caballero et al, ; Högestätt et al, ; Mallet et al, ; Ottani, Leone, Sandrini, Ferrari, & Bertolini et al, ). A recent study also identified AM404 as an antiviral agent that effectively inhibits replication of the dengue virus by binding with the NS4B protein (van Cleef, Overheul, Thomassen, Marjakangas, & van Rij, ). To our knowledge, no studies exist on the antibacterial activities of AM404 and its mode of action.…”
Section: Discussionmentioning
confidence: 99%